2019
DOI: 10.3390/ijms20081976
|View full text |Cite
|
Sign up to set email alerts
|

High Body Mass Index is Associated with Elevated Blood Levels of Progerin mRNA

Abstract: Obesity is a well-described risk factor resulting in premature aging of the cardiovascular system ultimately limiting longevity. Premature cardiac death and aging is the hallmark of Hutchinson–Gilford syndrome (HGPS), a disease caused by defined mutations in the lamin A gene leading to a shortened prelamin A protein known as progerin. Since small amounts of progerin are expressed in healthy individuals we aimed to investigate the association of Body-Mass-Index (BMI) with respect to expression of progerin mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Since we previously also found a positive association between progerin mRNA, overweight (body mass index), and inflammation (hs-CRP) our data may suggest a positive link between cardiovascular aging and inflammation in patients with heart failure [ 10 ]. Increased progerin mRNA expression was related to LV dysfunction, and progerin expression in the nucleus of cardiomyocytes was related to apoptotic cell death in patients with dilative cardiomyopathy [ 9 ].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Since we previously also found a positive association between progerin mRNA, overweight (body mass index), and inflammation (hs-CRP) our data may suggest a positive link between cardiovascular aging and inflammation in patients with heart failure [ 10 ]. Increased progerin mRNA expression was related to LV dysfunction, and progerin expression in the nucleus of cardiomyocytes was related to apoptotic cell death in patients with dilative cardiomyopathy [ 9 ].…”
Section: Discussionmentioning
confidence: 57%
“…Diagnoses of heart failure etiology are depicted in Table A1 . Most of the patients suffered from DCM, followed by ICM, hypertrophic cardiomyopathy and other reasons for heart failure [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has shown that elevated blood levels of progerin can be detected in people with obesity, suggesting a cause for premature aging of the cardiovascular system. Therefore, progerin might be measured in blood samples and be adapted for diagnostic measurements (Messner et al, 2019). Another marker of cellular senescence, which can be investigated in cultured cells (e.g., based on punch skin biopsy), are senescent-associated histone foci (SAHF).…”
Section: Senescence-related-biomarkersmentioning
confidence: 99%